2010
DOI: 10.1364/ao.49.000463
|View full text |Cite
|
Sign up to set email alerts
|

Blue surface-emitting distributed feedback lasers based on TPD-doped films

Abstract: Single-mode second-order distributed feedback (DFB) lasers with low threshold, based on polystyrene films doped with 30 wt: % of the hole-transporting organic molecule N,N 0 -bis (3-methylphenyl)-N,N 0 -diphenylbenzidine (TPD) are reported. The laser emission wavelength was tuned between 415 and 427 nm by film thickness variation. The effectiveness of the DFB grating in improving the laser performance is evidenced by the observation of linewidths and laser thresholds lower than those of the amplified spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
1
25
2
Order By: Relevance
“…Some preliminary discussions at this respect can be found elsewhere. 17,22 We also investigated the effect of changing the size of the excitation beam on the operational lifetime of the devices. As expected, when excitation was performed with spot areas larger than A crit , so the energy and power density thresholds were the same, similar lifetimes (considering that the experimental errors is around 10%) were obtained.…”
Section: -mentioning
confidence: 99%
“…Some preliminary discussions at this respect can be found elsewhere. 17,22 We also investigated the effect of changing the size of the excitation beam on the operational lifetime of the devices. As expected, when excitation was performed with spot areas larger than A crit , so the energy and power density thresholds were the same, similar lifetimes (considering that the experimental errors is around 10%) were obtained.…”
Section: -mentioning
confidence: 99%
“…Despite the limited amount of information regarding the film thickness dependence of the ASE properties on waveguides, there have been numerous reports investigating the influence of this parameter in the context of organic DFB lasers [13,[18][19][20][21][22]. This is because varying h constitutes the simplest way to tune the emission wavelength (λ DFB ) of the devices, tunability being one of the most attracting properties of organic materials as laser active media.…”
Section: Introductionmentioning
confidence: 99%
“…The available tuning range is limited by the gain spectral width and at lower wavelengths by the overlap with the absorption spectrum. Consequently, in the literature in which the influence of h on the DFB emission threshold has been analyzed, results have been explained in terms of the proximity of the emission wavelength to the maximum of the gain spectrum [13,[18][19][20][21][22]. In some cases, it was suggested that some other parameters, such as the confinement of the waveguide mode [13,18] or the presence of competing higher order modes [19], could play a role.…”
Section: Introductionmentioning
confidence: 99%
“…λ max = 372 nm [19]. The pattern recorded is obtained by the interference of the direct beam (5 cm diameter) and the reflected beam in a mirror attached with a 90° angle to the sample holder (a scheme of the setup can be found in [4]). The light intensity pattern was uniform over the whole sample area.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…In the context of DFB lasers with active materials in the form of organic waveguide films, the most common geometry consists in a surface-relief grating engraved on top of a conventional substrate, such as glass or SiO 2 , over which the organic active film is deposited [2][3][4][5]. Typically, gratings are recorded over an appropriate resist with EBL, NIL or HL, and then transferred to the substrate by ion-beam etching.…”
Section: Introductionmentioning
confidence: 99%